Effect of artificial insemination in comparison to natural mating on the reproductive performance and profitability of smallholder pig production system in Indian Himalaya - Singh, Mahak; Mollier, R. Talimoa; Pongener, Nungshitula; Patton, R. N.; Yadav, Rekha; Chaudhary, J. K.; Katiyar, Rahul; Babu, Subhash; Rajkhowa, D. J.; Mishra, V. K. (Frontiers in Sustainable Food Systems, 2022)
In fragile ecosystems, small-holder pig production systems provide food and nutritional security to resource-poor communities. Pigs are the main livestock raised by indigenous communities in the Himalayan region of India, but their productivity is low because of several reasons. The present study aimed to study the pig herd size and to evaluate the impact of artificial insemination (AI) on profitability and sustainability in small holder pig production system. A total of 612 artificial inseminations were carried out in 483 sows in the farmer's field along with 114 sows that underwent natural breeding. A comparison was made between the reproductive performance of sows following artificial insemination and natural breeding. The profitability and economics of AI and natural breeding was also compared. The mean pig population varied from 4.75 to 6.42 in the study region. The farrowing rate, total born piglets (TBP) and live born piglets (LBP) were significantly higher (P<0.001) in artificially inseminated sows compared to naturally bred sows. Farrowing rate (P=0.005), TBP and LBP were significantly (P<0.001) higher in sows inseminated by female inseminator as compared to male inseminator. The insemination by uneducated farmers resulted in significantly (P=0.002) lower farrowing rate, TBP (P<0.001), LBP (P<0.001) and AI per farrowing (P=0.042). The farmers who did the AI on third times and more than third times recorded significantly (P<0.001) higher farrowing rate, TBP and LBP. The farrowing rate was significantly (P<0.001) less in sows away more than 30 km from semen centre. The net return per sow was significantly higher (P<0.001) in artificially inseminated sows. The AI resulted in 87.33 % increase in net returns per farrowing as compared to natural breeding. In conclusion, AI in small-holders pig production systems has the potential to sustainably improve the profitability as well as the food and nutritional security of resource poor farmers.